Lipemia: an overrated interference?...reprinted from the British Journal of Biomedical Science 2003 with permission of the publisher - Anderson NR; Slim S; Gama R; Holland MR (Journal of Continuing Education Topics & Issues, 2005)
Reagent method sheets for analysis of common serum analytes often highlight the possibility of interference from lipemia but the information given is often brief and may not be instrument-specific. This study assesses the degree of interference from lipemia in a range of common serum analytes on the Bayer Opera (with a serum blank) using a commercial polymer, LipoClear, as a lipid-clearing agent. Serum samples (mean serum triglyceride 6.89 [range 0.58-28.4] mmol/L) are analyzed for 14 common chemistry analytes and the results compared be-fore and after treatment with LipoClear. Results showed no significant critical differences in analyte values before and after treatment, except for an expected fall in total protein, phosphate, cholesterol and triglyceride concentrations. Most of the common analytes in use on the Bayer Opera are not subject to interference from lipemia; how-ever, we recommend that where method sheets indicate interference from lipemia then this should be quantified for the analyte in question.